Leadership in English Language Teaching and Learning: A Systematic Review of the Past Decade - Chen, Yuqian; Wang, Siqi; Hu, Xiaofeng; Maowulan, Shadanguli; Jiang, Yutong (Forum for Linguistic Studies, 2025)
Leadership in English language teaching and learning is often discussed but seldom synthesized as a distinct focus; the evidence remains fragmented and indirect. This systematic review integrates empirical studies published from 2014 to 2024, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Searches in Web of Science and Scopus, screening, and independent expert checks yielded 26 studies for thematic analysis addressing three questions: (1) the types of leadership investigated and conceptualized; (2) the characteristics, processes, and impacts of teacher- and student-initiated leadership; and (3) the methodological, theoretical, and contextual forces shaping the field. Findings show that leadership is treated as a practice rather than a position, spanning principal and department leadership; distributed leadership that centers on English for speakers of other languages; teacher leadership (pedagogical and relational); supervisory leadership; interactional leadership enacted in classroom discourse; shared or collective leadership in project-based and professional-learning settings; and student or peer leadership. Teacher leadership blends a relational stance with deliberate task and method design, often shifting toward facilitation in technology-mediated courses and linking to participation, perceived learning, achievement, and equity. Student leadership is emergent, role-fluid, and task-bound, predicting participation and dividing functions across offline idea generation and online evidence synthesis and revision. Qualitative case studies, interviews, and conversation analysis predominate, complemented by survey-based modeling and emerging longitudinal and ethnographic designs; transformational, instructional, distributed, communities of-practice, concept-based, and shared-leadership perspectives frame the inquiry. Implications include strengthening department-level coordination and whole-school provision for multilingual learners, preparing teachers for both relational work and design/facilitation (especially online), and structuring student leadership via interdependent tasks, rotating roles, and explicit discourse norms. Highlights Leadership in English language teaching is understood as practice rather than position, spanning teacher, student, supervisory, and shared forms. Teacher leadership blends relational support with pedagogical design, while student leadership is role-fluid, task-bound, and strongly predicts participation. Research has expanded methodologically and theoretically, with increasing attention to distributed, interactional, and context-sensitive leadership in English language teaching.